Lung ultrasound predicts histological lung injury in a neonatal model of acute respiratory distress syndrome. Issue 11 (10th August 2020) - Elsayed, Yasser N.; Hinton, Martha; Graham, Ruth; Dakshinamurti, Shyamala
Abstract: Rationale: Point‐of‐care ultrasound (POCUS) is used to evaluate pulmonary edema in adults with acute respiratory distress syndrome (ARDS). Its use has not been validated in neonatal models. Objectives: We compared an in vivo lung ultrasound score against clinical and histological markers of acute lung injury, in a neonatal animal model, hypothesizing that POCUS would sensitively diagnose early acute lung injury in neonates and discern its severity. Methods: Fifteen anesthetized, ventilated 3‐day‐old neonatal piglets were divided into controls, moderate lung injury, or severe lung injury by graded treatment with oleic acid. Degree of lung injury was quantified at baseline, immediately after oleic acid administration, and 1 hour after the evolution of acute lung injury, by blood gases, ventilation parameters and calculated oxygenation deficit; hemodynamic indices by echocardiography, and lung ultrasound obtained in an 8‐region grid of anterior and posterior zones, semi‐quantitatively analyzed by a blinded observer. Lungs were inflation‐fixed postmortem at last mean airway pressure, for histological assessment. Results: Acute lung injury manifested in oleic acid‐treated groups as dose‐dependent capillary leak causing intravascular depletion and cardiac failure, hypoxemia with increasing intrapulmonary shunt fraction, decreased lung compliance, and resistance. Ultrasound scores of anterior regions distinguished moderate from severe injury; scores in posterior regions reached maximum values immediately after lung injury. POCUS score correlated with calculated intrapulmonary shunt fraction ( R 2  = .65) and with histological injury score ( R 2  = .61), P  < .01. Conclusion: We conclude that POCUS may be valuable in neonates for early quantification of acute lung injury or ARDS; and that nondependent ultrasound regions clearly distinguish severity of pulmonary edema.